The Effect of Endolymphatic Hydrops and Mannitol Dehydration Treatment on Guinea Pigs - Wang, Shu-Qi; Li, Chen-Long; Xu, Jing-Qi; Chen, Li-Li; Xie, You-Zhou; Dai, Pei-Dong; Ren, Liu-Jie; Yao, Wen-Juan; Zhang, Tian-Yu (Frontiers in Cellular Neuroscience, 2022)
Background: Endolymphatic hydrops (EH) is considered as the pathologic correlate of Menière’s disease (MD) and cause of hearing loss. The mechanism of EH, remaining unrevealed, poses challenges for formalized clinical trials. Objectives: This study aims to investigate the development of hearing loss, as well as the effect of dehydration treatment on EH animal models. Methods: Different severity of EH animal models had been created for this study. Laser Doppler vibrometer (LDV) and auditory brainstem responses (ABR) were used to study the effect of EH and the dehydration effects of mannitol. LDV was used to measure the vibration of the round window membrane (RWM) reflecting the changes of inner ear impedance. ABR was adopted to evaluate the hearing changes. Furthermore, tissue section and scanning electron microscopy (SEM) observations were applied to analyze the anatomical change to the cochlea and outer hair cells. Results: The RWM vibrations decreased with the severity of EH, indicating an increase in the cochlear impedance. The dehydration therapy lowered the impedance to restore acoustic transduction in EH 10-day, EH 20-day animal models. Simultaneously, the ABR thresholds increased in EH models and restored after dehydration. Moreover, a difference in hearing was found between ABR and LDV results in severe EH animal models, and the dehydration therapy was less effective, indicating a sensorineural hearing loss (SNHL). Conclusion: EH causes hearing loss by increasing the cochlear impedance in all tested groups, and mannitol dehydration is an effective therapy to restore hearing. However, SNHL occurs for EH 30-day animal models, limiting the effectiveness of dehydration. Our results suggest a use of dehydrating agents in the early stage of EH.